The possibility of catching severe COVID-19 disease with cardio-renal manifestation after the first dose of the BNT-162b2 vaccine: A case report - Randa Tabbah; Nagi Azzi; Rachoin Rachoin (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
Introduction: Since November 2019, coronavirus disease 2019 (COVID-19) has continued to spread across the world in an unpredictable way. In December 2020, the US Food and Drug Administration (FDA) issued Emergency Use Authorizations for two mRNA-based vaccines for prevention of COVID-19 including the BNT-162b2 or Pfizer-BioNTech vaccine. The window period of the vaccine efficacy and baseline patients' characteristics remain factors to be taken into consideration in all cases.  Clinical presentation: A 92-years old lady known to have a history of severe Aortic Stenosis (AS), bedridden years ago received her first BNT-162b2 shot as per country protocol. Five-days later, a routine lab-test revealed hypereosinophilia. Ten-days after vaccination, patient developed a low-grade fever 38.2 with cough, tachycardia of 160bpm and SpO2= 95% on 2 liters of oxygen. She was dehydrated and had oliguria. CT-scan revealed a bilateral pleural effusion with no other relevant findings and EKG was in favor of rapid atrial fibrillation (AFib) of 160 bpm, back to sinus after digoxin 0.25mg IV. COVID-PCR came back positive, and patient was discharged home by the COVID-19 team for symptomatic treatment and follow up. Two-days later, patient became sicker with shortness of breath, loss of appetite and higher fever. She was admitted then, and lab-tests revealed very high levels of hepatic and pancreatic enzymes in addition to high levels of cardiac-enzymes revealing cardiac injury. Moreover, inflammatory labs were high and same for her creatinine levels revealing a cardiorenal syndrome. Patient was on corticosteroids and hydration for several days with improvement of her vital signs and lab-tests with hepatic enzymes close to normal values but an increase in WBC with CRP levels remaining low. Neurologic status was poor. CT brain revealed a small ischemic stroke on the left side with weakness and hemiparesis on the right. Echocardiography revealed a decrease in LV function with global hypokinesis. After 1week, the neurologic status of the patient declined, and invasive ventilation was needed. 3 days after intubation patient died. Conclusion: Cardiorenal syndrome is possible after a first dose of covid-19 vaccine. That is why masking and social distancing should be maintained to prevent fully immunized subjects from acting as human vectors to non-immunized ones. No protection for patients after first shot of vaccine within the window of 12 day.  Learning objectives  - Masking and social distancing should be maintained to prevent contracting COVID-19 and thereafter to prevent immunized subjects from acting as human vectors  - The presence of eosinophilia right after a COVID-19 vaccination should rather be attributed to the vaccine than to the disease, because of the demonstrated protective role of that eosinophilia. - There is no protection before the 12th day of the first vaccine dose, with a gradual improvement thereafter before reaching 70% protection on the 21st day. - The cardiovascular manifestations of COVID-19 include atrial arrhythmias as being the most frequent, with atrial fibrillation as the most common and ominous for the patient's outcome because it denotes an extensive myocardial injury.